INNOVATIVE STRATEGIES FOR IMPROVING PROBIOTIC VIABILITY USING AVOCADO-BASED PREBIOTICS AND NANOTECHNOLOGY - M., JATIN; ADHIKARI, BISHOP; J., ALIN BOSE; KUMAR, PIYUSH; KUMAR, RAMAN RAJESH (International Journal of Applied Pharmaceutics, 2025)
Probiotics are increasingly incorporated into functional foods; however, their efficacy is hindered by poor stability under processing and Gastrointestinal (GI) conditions. Avocado fruit and its waste contain fermentable fibers (pectin, resistant starch) and bioactive compounds that act as prebiotics. Current probiotic stabilization strategies often overlook the importance of nutrient synergy and sustainability. This review reveals a gap: conventional carriers (alginate, inulin, etc.) provide protection but little additional growth substrate, whereas avocado fibers offer both nourishment and encapsulation potential. Nanotechnology has emerged as a revolutionary field with immense potential in various industries, including the delivery of nutraceuticals. Combining avocado pectin/resistant starch with cellulose nanofibers (from plants or microbial cellulose) is innovative because it co-delivers prebiotics and mechanical defense. Future work should address remaining challenges: regulatory evaluation of edible nanocellulose and novel food status, comprehensive safety testing for ingestible nano-carriers, and deeper mechanistic studies on how avocado polysaccharides and phenolics modulate probiotic metabolism. Overall, integrating avocado-derived prebiotics into nanocellulose matrices appears to be a promising strategy for robust, targeted probiotic delivery and warrants further experimental and clinical validation.